Mekaar Financing and Business Capacity Development Program to Increase Turnover and Customer Loyalty - Jimi Firmansyah (Formosa Journal of Sustainable Research, 2023)
Mekaar PNM program financing is one of the products developed by PT. Madani National Capital, which was formed by the government under the Ministry of BUMN, which is now formed in the Ultra Micro Holding which focuses on Ultra Micro financing for underprivileged mothers with group lending or in the form of groups. Meanwhile, the Business Capacity Development Program (PKU) aims to bring together small businesses and training. This study seeks to analyze the role of financing the Mekaar program and business capacity building in order to increase turnover and customer loyalty at the Subang branch. This study uses a qualitative descriptive approach with interview techniques, analysis using the Nvivo 12pro application. The informants or respondents used were division heads, deputy division heads of PT. PNM, Unit Heads, Account Officers and customers of PT. PNM Subang Branch consisting of 14 respondents. It is hoped that the results of this study can analyze the role of PNM Mekaar financing and business capacity building programs that have a positive influence on turnover and customer loyalty